Lambliasis in Children. Epidemiology, Clinical Picture, Diagnosis - A.A. Konyushevskaya; N.V. Sidorenko; L.V. Soroka; O.S. Detsik (Zaslavsky O.Yu., 2014)
The article considers the lambliasis - one of most common protozoan diseases in children. This article gives a review of literature on epidemiology, clinical picture and diagnosis of lambliasis in children as well as own observations.